Pendekatan Konseling Afirmasi Positif untuk Peningkatan Prestasi dan Pengurangan Perilaku Negatif - Baeda, Abd. Gani; Tukatman, Tukatman; Siagian, Heriviyatno Julika; Nasus, Evodius; Syahruddin, Muh. (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
Academic performance and personal conduct are two interrelated facets within the field of education. Nonetheless, numerous obstacles, including insufficient motivation, diminished self-confidence, and adverse conduct, can impede the achievement of optimal learning results. This initiative seeks to employ a positive affirmation counseling methodology to improve academic performance and mitigate adverse behaviors among participants. The applied strategy encompasses problem identification via focus group discussions, execution of individual and group-based positive affirmation counseling, and assessment of outcomes through questionnaires and observation. The results demonstrate that positive affirmation approaches significantly enhance learning motivation, transform participants' mindsets, and diminish negative behaviors that previously obstructed the learning process. Participants indicated enhanced self-confidence and improved stress management in academic settings. In conclusion, the positive affirmation method has demonstrated efficacy in cultivating healthy mindsets and enabling individuals to realize their academic and social potential.